Synthesis and characterization of core-shell nanoparticles and their application in dental resins. (October 2020) - Roshanali, Maryam; Nodehi, Azizollah; Atai, Mohammad
Abstract: The aim of this study was to synthesize acrylic core-shell particles and silica-loaded core-shell hybrid particles through emulsion polymerization. Also this work examined the influence of synthesized nanoparticles loading in a Bis-GMA/TEGDMA resin matrix on some mechanical properties of the dental composite resins. Core-shell particles consisting of polybutyl acrylate (PBA) rubbery core and polymethyl methacrylate (PMMA)/polystyrene (PS) shell were synthesized by seeded emulsion polymerization. For preparing the core-shell hybrid particles, first silica particles with diameters of about 68 nm were synthesized based on the Stöber process. Then the surface of silica particles was treated with ɣ-MPS. Afterwards, polymeric shell was coated on silica nanoparticles through emulsion polymerization. The morphology of core-shell particles was examined by SEM/TEM. Mechanical properties (fracture toughness, flexural strength and flexural modulus) of the photo-cured Bis-GMA/TEGDMA dental resins/composites filled with different mass fractions of synthesized nanoparticles were tested, and analysis of variance (ANOVA) was used for the statistical analysis of the acquired data. Formation of glassy shell on PBA core in core-shell particles, grafting of ɣ -MPS onto the silica particles and encapsulation of modified silica by polymeric shell in core-shell hybrid particles were confirmed using various analytical techniques. The results of mechanical tests showed that fracture toughness of Bis-GMA/TEGDMA dental resins improved about 35% by the inclusion of 5 wt% silica-loaded core-shell hybrid particles with little effect on flexural strength. This study shows that incorporation of proper amount of hybrid core-shell particles in dental composites can improve their fracture toughness and thus may extend their service life. Graphical abstract: Image 1 Highlights: Acrylic core-shell nanoparticles and silica loaded core-shell hybrid particles were prepared and characterized. The effect of addition of core-shell particles on mechanical properties of Bis-GMA/TEGDMA dental resins was examined. Silica-loaded core-shell hybrid particles were efficient in improving the fracture toughness of Bis-GMA/TEGDMA resins.